1995
DOI: 10.1182/blood.v86.2.463.bloodjournal862463
|View full text |Cite
|
Sign up to set email alerts
|

Primordial germ cells are capable of producing cells of the hematopoietic system in vitro

Abstract: The identity of the cells giving rise to the hematopoietic system in the mouse embryo are unknown. The results presented here strongly suggest that hematopoietic cells are derived from a nonhematopoietic cell population that has been previously thought to give rise to the germ cells. These cells are called primordial germ cells (PGCs) and can be recognized as large cells showing blebbing and pseudopodial extrusions on their surface. They are alkaline phosphatase (AP) positive and possess a stage-specific embry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(32 citation statements)
references
References 39 publications
2
29
0
1
Order By: Relevance
“…More importantly, to support a link between PGCs and VSELs as precursors of long-term repopulating HSCs (LT-HSCs), 45,70,71 we observed that VSELs and HSCs express mRNA for several pituitary and gonadal hormone receptors as well as highly express Sall4, an early-development marker shared by germ and hematopoietic cells. 72,73 Finally, in direct in vivo and in vitro experiments, we confirmed that the quiescent population of BM-residing VSELs, like HSCs, expands in response to stimulation by androgens (danazol) and pituitary gonadotropins such as pregnant mare serum gonadotropin (PMSG), luteinizing hormone (LH), and folliclestimulating hormone (FSH).…”
Section: The Developmental Origin Of Vsels Explains the Epigenetic Chsupporting
confidence: 53%
“…More importantly, to support a link between PGCs and VSELs as precursors of long-term repopulating HSCs (LT-HSCs), 45,70,71 we observed that VSELs and HSCs express mRNA for several pituitary and gonadal hormone receptors as well as highly express Sall4, an early-development marker shared by germ and hematopoietic cells. 72,73 Finally, in direct in vivo and in vitro experiments, we confirmed that the quiescent population of BM-residing VSELs, like HSCs, expands in response to stimulation by androgens (danazol) and pituitary gonadotropins such as pregnant mare serum gonadotropin (PMSG), luteinizing hormone (LH), and folliclestimulating hormone (FSH).…”
Section: The Developmental Origin Of Vsels Explains the Epigenetic Chsupporting
confidence: 53%
“…In support of this concept, both PGCs and VSELs are reportedly able to give rise to HSCs and EPCs 55,56,[90][91][92] . Moreover, PGC-derived precursors of gametes, VSELs, and HSCs express several functional sex hormone receptors and the erythropoietin (EpO) receptor.…”
Section: The Hierarchy Of the Stem Cell Compartment In Embryonic And mentioning
confidence: 97%
“…Much emphasis has recently been placed on this intraembryonic source of HSC [9,54,55,30,40,50,56]. However, interpretation of the AGM results is complicated by the fact that primordial germ cells, which are localized to this region, have the potential to generate hematopoietic progenitor cells [57][58][59] as, indeed, do embryonic stem cells [60][61][62][63].…”
Section: On Yolk Sac (Aa41 + Wga Bright ) Fetal Liver (Aa41 + Wgmentioning
confidence: 99%